Reinforced concrete ring beams [non-linear finite element analysis (NLFEA)] - Al Qaicy, Haider Hamad Ghayeb; Marsono, Abdul Kadir; Hejazi, Farzad (Textroad Publishing Corporation, 2014)
Ring beams are encountered in dome, circular reservoir and silo structure. Reinforced concrete ring beams supported by equally spaced columns have been used for the construction of silo structure,where the large free space is needed at the ground level. In this paper, three reinforced concrete ring beams supported on four equally spaced columns have been analyzed by using non-linear finite element analysis (NLEFA) to predict the ultimate strength, mechanismof failure, crack pattern and deformed shape. The geometrical and material properties of the ring beams are similar except of its cross sectional depth and the properties of reinforcements. The NLFEA results indicate that the failure modes of the ring beams are dependent on its (depth/span) ratio (the span/depth ratio has been taken as straight beams). The tension stiffening value from 0.002 to 0.003 is suggested to use in the non-linear finite element analysis (NLFEA)of ring beams.